f(2+a)=5(2+a)-7

Simple and best practice solution for f(2+a)=5(2+a)-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for f(2+a)=5(2+a)-7 equation:


Simplifying
f(2 + a) = 5(2 + a) + -7
(2 * f + a * f) = 5(2 + a) + -7

Reorder the terms:
(af + 2f) = 5(2 + a) + -7
(af + 2f) = 5(2 + a) + -7
af + 2f = (2 * 5 + a * 5) + -7
af + 2f = (10 + 5a) + -7

Reorder the terms:
af + 2f = 10 + -7 + 5a

Combine like terms: 10 + -7 = 3
af + 2f = 3 + 5a

Solving
af + 2f = 3 + 5a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-5a' to each side of the equation.
af + -5a + 2f = 3 + 5a + -5a

Reorder the terms:
-5a + af + 2f = 3 + 5a + -5a

Combine like terms: 5a + -5a = 0
-5a + af + 2f = 3 + 0
-5a + af + 2f = 3

Add '-2f' to each side of the equation.
-5a + af + 2f + -2f = 3 + -2f

Combine like terms: 2f + -2f = 0
-5a + af + 0 = 3 + -2f
-5a + af = 3 + -2f

Reorder the terms:
-3 + -5a + af + 2f = 3 + -2f + -3 + 2f

Reorder the terms:
-3 + -5a + af + 2f = 3 + -3 + -2f + 2f

Combine like terms: 3 + -3 = 0
-3 + -5a + af + 2f = 0 + -2f + 2f
-3 + -5a + af + 2f = -2f + 2f

Combine like terms: -2f + 2f = 0
-3 + -5a + af + 2f = 0

The solution to this equation could not be determined.

See similar equations:

| h+19/19=2 | | 3=-7 | | 950+700+4x=850+200+9x | | f(4)=5(4)-7 | | +5=1+k | | 11-4x=0.5 | | 19+-5p=-1 | | (3/5)w-(1/7)=(-3/7)w+(3/7) | | 7r=-7 | | 12-(1/26)(2x)=6-(1/26)(x) | | 7x*8k=8x-17k | | 5x+2/7x-6 | | 4y^2-5y^2+7y^2= | | [SQRT(x+3)]=2[SQRT(x)] | | x^3+2x^2-6x=12 | | (5/4)y-(3/8)=(7/2)y+(3/8) | | 0.1=.07+x(0.12) | | 2(x/3-3)=16 | | 3(3n-3)=-54 | | (9x-3)*(-0.7)= | | 6+9z=7 | | -6v+11=-4v+1 | | (-5i)+(I)= | | 2x^2+58=20x | | (-7)(8)-(-6)(-2)= | | 6x^2+2x-17=0 | | 1.5z=z | | 8x+10+2x=90 | | (1/x)+(1/x+3)=(1/4) | | -9z-9=-4z+6 | | 8+-25=-57 | | -6x-5=31 |

Equations solver categories